1999
DOI: 10.1073/pnas.96.18.10332
|View full text |Cite
|
Sign up to set email alerts
|

Calcium signaling induces acquisition of dendritic cell characteristics in chronic myelogenous leukemia myeloid progenitor cells

Abstract: Effective host T lymphocyte sensitization to malignant cells depends on successful antigen presentation. In this study, we examined the capacity of malignant myeloid progenitor cells of patients in the chronic phase of chronic myelogenous leukemia (CML) to acquire characteristics of activated dendritic cells ( Recent clinical observations indicate that T lymphocytes can play an important therapeutic role in chronic myelogenous leukemia (CML) (1, 2). Donor lymphocyte infusions are effective in inducing complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 26 publications
1
18
2
Order By: Relevance
“…For example, stimulation of B lymphoma cells with db-cAMP alone has been reported to induce surface CD80 expression (36). In a similar vein, stimulation of chronic myelogenous leukemia myeloid progenitor cells with a calcium ionophore has also been found to result in CD80 up-regulation (47). However, in both cases the concentrations of stimulators used were significantly higher than those used in this study (36,47).…”
Section: Cross-talk Between Second Messengers Overcomes Individual Cocontrasting
confidence: 45%
See 1 more Smart Citation
“…For example, stimulation of B lymphoma cells with db-cAMP alone has been reported to induce surface CD80 expression (36). In a similar vein, stimulation of chronic myelogenous leukemia myeloid progenitor cells with a calcium ionophore has also been found to result in CD80 up-regulation (47). However, in both cases the concentrations of stimulators used were significantly higher than those used in this study (36,47).…”
Section: Cross-talk Between Second Messengers Overcomes Individual Cocontrasting
confidence: 45%
“…In a similar vein, stimulation of chronic myelogenous leukemia myeloid progenitor cells with a calcium ionophore has also been found to result in CD80 up-regulation (47). However, in both cases the concentrations of stimulators used were significantly higher than those used in this study (36,47). Therefore, it occurred to us that the cross-talk between Ca i 2ϩ and cAMP may well serve to minimize individual concentrations required for the induction of CD80 expression.…”
Section: Cross-talk Between Second Messengers Overcomes Individual Cocontrasting
confidence: 40%
“…Because leukemic cells may lack one or more components of membrane and proximal signal transduction pathways, direct activation of downstream pathways may drive DC differentiation more effectively (30). We have shown that PKC activation by the 2,3-diacylglycerol analog PMA induces DC differentiation in acute myeloid leukemia (AML) blasts (26), while others have demonstrated the same following direct activation of intracellular calcium signaling by calcium ionophore (CI) (25,27,28,31). Although these studies and model systems have also suggested which upstream signals initiate DC differentiation, the signal transduction pathways and genetic events involved remain largely undefined.…”
Section: Hronic Myelogenous Leukemia (Cml)mentioning
confidence: 99%
“…DC generated directly from leukemic blasts potentially overcome the problems of other anti-tumor DC vaccine approaches, where normal progenitor-derived DC are exogenously loaded with a limited number of known tumor-specific Ags (17,18). Ex vivo differentiation of DC from both normal and leukemic progenitors can be driven by both receptor-mediated exogenous stimuli (i.e., cytokine combinations GM-CSF, IL-4, TNF-␣, and CD40 cross-linking) (9, 14, 19 -22) and agents that directly activate intracellular signaling pathways (calcium ionophores (intracellular calcium) and phorbol esters (protein kinase C (PKC)) (23)(24)(25)(26)(27)(28)(29). Because leukemic cells may lack one or more components of membrane and proximal signal transduction pathways, direct activation of downstream pathways may drive DC differentiation more effectively (30).…”
Section: Hronic Myelogenous Leukemia (Cml)mentioning
confidence: 99%
“…CMML-derived DCs are potent stimulators of the allogeneic mixed lymphocyte reaction (MLR) and may serve as a cellular vaccine to induce anti-tumor immunity in patients with CMML (23). Some researchers have successfully induced chronic myelogenous leukemia (CML) cells to become CML-DCs using GM-CSF and IL-4, and the CML-DCs produced appear no different from normal DCs in terms of their ability to stimulate the proliferation of T lymphocytes (3,24,25). CML-DCs can express high levels of co-stimulatory molecules such as CD1a, CD86, CD40, CD80, and CD83 and stimulate autologous T cells or human leukocyte antigen (HLA)-compatible donor T cells to proliferate substantially and start a CML-specific cytotoxic immune response.…”
Section: Dcs Produced From Primary Leukemia Cellsmentioning
confidence: 99%